Manufacturing and Study of Mechanical Properties, Structure and Compatibility with Biological Objects of Plates and Wire from New Ti-25Nb-13Ta-5Zr Alloy - Sergey V. Gudkov; Alexander V. Simakin; Mikhail A. Sevostyanov; Sergey V. Konushkin; Monika Losertová; Alexander Yu. Ivannikov; Alexey G. Kolmakov; Andrey Yu. Izmailov (Metals, 2020)
A Ti–25Nb–13Ta–5Zr alloy was produced and studied in this work, and plates and wires were made from this alloy. It is shown that the Ti–25Nb–13Ta–5Zr alloy has the required mechanical properties and a β-crystal phase. Microstructures were present on the surface of the alloy with a height of several hundred nm, located at a distance of 1.5–2 μm from each other. Ti–25Nb–13Ta–5Zr was superior to nitinol in terms of the formation of long-living reactive protein species and the generation of reactive oxygen species. Cell cultivation on Ti–25Nb–13Ta–5Zr alloy surfaces revealed a significant mitotic index (2%) and a small number of nonviable cells (<5%). The cells were actively attached and spread over the alloy. The biocompatibility of Ti–25Nb–13Ta–5Zr was verified by experiments on the implantation of the alloy in the form of plates and coiled wires. The surface morphology of the specimens after biological trials was not significantly altered. The experimental data we obtained suggest that Ti–25Nb–13Ta–5Zr is suitable for potential applications in biology and medicine.